The importance of champions: developing national guidance for the external management of residential child care establishments in Scotland - Louise Hill; Neil Gentleman (Scottish Journal of Residential Child Care)
External managers can play a critical role in safeguarding children and young people, supporting staff and championing residential child care across local authority, voluntary and independent settings. Despite the recommendations stemming from inquiries into abuse and neglect in residential child care, there has been relatively little attention given to the role of the external manager. This article outlines the development of the National Guidance for External Management for Residential Child care Establishments in Scotland. The guidance was informed through a national scoping exercise involving external managers, unit managers, inspection bodies and advocacy providers. Drawing on national and local expertise, the authors highlight the importance of keeping the child at the centre, creating a positive culture and ensuring compliance to effectively fulfil the external manager role. The opportunities and challenges of implementing the Guidance are discussed.